ACCESSIO (AKCESJA) W TERMINOLOGII RZYMSKIEGO PRAWA PRYWATNEGO - Świrgoń-Skok, Renata (Zeszyty Prawnicze, 2017)
The ‘accessio’ (accession) in the Terminology of Roman Private Law Summary The term accessio (accession) in the terminology of Roman private law did not only denote union and confusion of things. It was a very general term used for defining various cases of property acquisition through union, growth of property, and it determined addition of a new obligation to an old one or addition of a supplementary contract, person or object to the obligation. In the Roman Law literature the term accessio is predominantly used for union of two things in accordance with the principle accessio cedit principali, i.e. the increase falls to the share of the principal. Moreover, the term accessio also denoted adding the duration of ownership of an object by the predecessor (accessio possessionis) or simply adding the duration (accessio temporis). In the sources for the Roman Law accessio temporis and possessionis are used interchangeably for determining specific actual states, which resolve issues connected with accession of ownership duration of the predecessor to the ownership duration of the last owner. Similarly in lexicons, accessio temporis is presented as a synonym of accessio possessionis. The aforementioned accession of ownership duration [of the predecessor by his successor under specific title was permissible with interdict aimed at protection against infringement of ownership of movable objects (interdictum utrubi), with prescription (usucapio) and charge of long time ownership (longi temporis praescriptio). Furthermore, accession also meant accessio personae that is addition of a person, i.e. additional creditor who, beside the principal creditor, could collect repayment of debt from debtor (adstipulator), or a person who additionally, beside the principal debtor, pledged to the creditor to repay the debt (adpromissor), or it is addition of a new obligation to an old one by means of contract of guaranty (fideiussio). With accessio personae, similarly to union of things in accordance with the principle of accessio cedit principali, there had to be two things, one of them determined as principal and the other - additional. Obviously, here occur two obligations, one treated as principal, and the other as additional or accessory. Moreover, accession also means accessio rei, that is addition of new article of service to obligation, that the debtor could render alternatively with the previous, which was possible with alternative obligation (obligatio alternativa) and alternative authorization (facultas alternativa).